1988
DOI: 10.1090/s0002-9947-1988-0943306-9
|View full text |Cite
|
Sign up to set email alerts
|

Definable sets in ordered structures. III

Abstract: ABSTRACT. We show that any o-minimal structure has a strongly o-minimal theory. Introduction.In this paper we prove that an arbitrary o-minimal structure M is strongly o-minimal. This was proved in [1] in the case when the ordering on M is dense.In §1 we show that for discrete M, o-minimal implies strongly o-minimal. This is, of course, a result on uniform finite bounds. The proof has some interesting differences with the dense case, partly because here one has to prove uniform bound results for functions defi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
8
0

Year Published

2000
2000
2016
2016

Publication Types

Select...
5
1
1

Relationship

0
7

Authors

Journals

citations
Cited by 37 publications
(8 citation statements)
references
References 4 publications
0
8
0
Order By: Relevance
“…In this paper when we say that some subset or function is definable, we mean it is first-order definable (possibly with parameters) in the sense of the structure M. A general reference for first-order logic is [9]. All the notions related to o-minimality can be found in [17,12,18], see also [19] for a nice overview. We start with the definition of an o-minimal structure: The field of reals R, <, +, ·, 0, 1 , the group of rationals Q, <, +, 0 , the field of reals with exponential function, the field of reals expanded by restricted pfaffian functions and the exponential function are o-minimal structures.…”
Section: O-minimality and Definabilitymentioning
confidence: 99%
See 1 more Smart Citation
“…In this paper when we say that some subset or function is definable, we mean it is first-order definable (possibly with parameters) in the sense of the structure M. A general reference for first-order logic is [9]. All the notions related to o-minimality can be found in [17,12,18], see also [19] for a nice overview. We start with the definition of an o-minimal structure: The field of reals R, <, +, ·, 0, 1 , the group of rationals Q, <, +, 0 , the field of reals with exponential function, the field of reals expanded by restricted pfaffian functions and the exponential function are o-minimal structures.…”
Section: O-minimality and Definabilitymentioning
confidence: 99%
“…The o-minimal structures [17,12,18,19] enjoy very nice finiteness properties. Regarding the above discussion it seemed interesting to define "o-minimal transition systems".…”
Section: Introductionmentioning
confidence: 99%
“…For instance, one can observe that, just as in the ominimal framework (see [9]), there is no proper weakly o-minimal expansion of (N , ≤) by "new" (non-definable) functions or relations. In fact, every convex set of (N , ≤) is also an interval (with endpoints in N ∪ {+∞}), so any weakly o-minimal expansion of (N , ≤) is o-minimal and, by [10], also strongly o-minimal. In [9] it was shown that such an expansion must only involve functions and relations which are already definable in (N , ≤).…”
Section: Some Counterexamplesmentioning
confidence: 99%
“…papers by Knight, Pillay, and Steinhorn (see [10,13,14]); a comprehensive treatment of the subject is also found in the survey text [6]. Throughout this paper, we will be considering expansions of o-minimal groups.…”
mentioning
confidence: 99%